2022
DOI: 10.3389/fonc.2022.985363
|View full text |Cite
|
Sign up to set email alerts
|

The role of BCL-2 family proteins in regulating apoptosis and cancer therapy

Abstract: Apoptosis, as a very important biological process, is a response to developmental cues or cellular stress. Impaired apoptosis plays a central role in the development of cancer and also reduces the efficacy of traditional cytotoxic therapies. Members of the B-cell lymphoma 2 (BCL-2) protein family have pro- or anti-apoptotic activities and have been studied intensively over the past decade for their importance in regulating apoptosis, tumorigenesis, and cellular responses to anticancer therapy. Since the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(147 citation statements)
references
References 162 publications
(174 reference statements)
1
84
0
Order By: Relevance
“…Apoptosis is a common form of cell death; hence we first explored the expressions of apoptotic proteins in A549/CDDP cells. The Bcl‐2 protein family functions as promoters or inhibitors of cell death, [47] and the p53 protein is critical to DNA damage, apoptosis and drug resistance [48] . The effect of FP and DFP on these proteins were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is a common form of cell death; hence we first explored the expressions of apoptotic proteins in A549/CDDP cells. The Bcl‐2 protein family functions as promoters or inhibitors of cell death, [47] and the p53 protein is critical to DNA damage, apoptosis and drug resistance [48] . The effect of FP and DFP on these proteins were determined by western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, BCL2 proteins are anti-apoptotic factors. Targeting these proteins by developing new drugs could help regulate apoptosis and thus anti-cancer therapy [40]. Increasing evidence has shown that the downregulation of CASP3 is correlated with the development of BC [39].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is initiated by proapoptotic proteins with one BH domain, such as borane. The Bcl‐2 protein family, encoded by the BIM gene, is one of the most active proapoptotic proteins 80 . The proapoptotic proteins Bcl‐2‐related X protein (BAX) and Bcl‐2 antagonist/killer (BAK) help activate proapoptotic proteins or promote protein pore formation.…”
Section: Mitochondrial Pathway Of Apoptosismentioning
confidence: 99%